Impact of Microwave Time on the Structure and Functional Properties of Glycosylated Soy 7S Globulins - Jixin Zhang; Tao Cui; Lan Zhang; Huiqing Xu; Jingguo Xu; Jun Wang (Foods)
This study examined the effects of varying microwave treatment durations (0–120 s) on the structural and functional properties of glycosylated soybean 7S protein. The results indicated that microwaving for 60 s significantly altered the structure of 7S, resulting in a more ordered protein configuration. The treated protein exhibited the largest particle size (152.3 nm), lowest polydispersity index (0.248), highest α-helix content (47.86%), and lowest β-sheet, β-turn, and random coil contents (12.33%, 16.07%, and 22.41%, respectively). It also showed the lowest endogenous fluorescence and surface hydrophobicity, and the highest thermal denaturation temperature (76.8 °C). Additionally, microwaving for ≤90 s led to increased peptide modifications, with carbamylation and deamidation being the most prevalent. A microwave treatment time of 60 s also notably enhanced the functional properties of glycosylated soybean 7S protein, optimizing water-holding capacity (6.060 g/g), emulsification activity, and stability (45.191 m2/g and 33.63 min). The foaming capacity was second only to the 120 s treatment (32% at 60 s versus 34% at 120 s), though the oil-holding capacity (22.73 g/g) and foaming stability (33.42%) were significantly lower than those of the controls. Microwave treatment durations exceeding or below 60 s led to the structural disintegration of the protein, diminishing most of its functional properties. This study explores the mechanism of how microwave processing time affects the structure and functional properties of glycosylated soybean 7S protein and identifies 60 s as the optimal microwave processing time. It meets the demands for healthy and delicious food in home cooking, providing scientific evidence for using microwave processing technology to enhance the nutritional value and quality of food.